Analisis Resiko Industri Kerajinan Pelepah Pisang “Pa’E Debog” di Desa Balenrejo - Lina Agustina; Deviana Diah Probowati (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2023)
. This study aims to determine whether the craft of silhouette painting, bags, and wallets "Pa'E Debog" is profitable or not and to find out how the level of risk and cost risk of "Pa'E Debog" is. Profits in this study were analyzed using the R/C Ratio while the cost risk and income risk were analyzed using the Coefficient of Variation analysis. The results showed that the craft of painting silhouettes, bags, and wallets was profitable. Silhouette painting has a value (R/C > 1), which is 1.24. Bag craft got a value of 1.86 (R/C > 1), and wallet craft got a value (R/C > 1) which was 1.94. While the results of the analysis of the coefficient of variation show that the business carried out by the banana midrib craft "Pa'E Debog" has the opportunity to lose or bear the risk of cost and income risk because the coefficient of variation of the craft of silhouette painting, bags, and wallets has a value (CV > 0.5 ) and (L < 0). Cost risk can be caused by the increase in the price of raw materials and limited human resources. Meanwhile, the income risk is caused by the erratic level of production and the Covid-19 pandemic so that sales have decreased.